Phase I study of intra-osseous co-transplantation of a single-unit cord blood and mesenchymal stromal cells with reduced intensity conditioning regimens - Wang, Jiasheng; Sanati, Farhad; Firoozmand, Amin; Fu, Pingfu; Kolk, Merle; Reese-Koc, Jane; de Lima, Marcos; Boughan, Kirsten; Cooper, Brenda; Caimi, Paolo; Gallogly, Molly; Otegbeye, Folashade; et al. (Frontiers in Oncology, 2023)
Cord blood (CB) is a valuable graft source for patients undergoing allogeneic hematopoietic cell transplant (HCT) who lack human leukocyte antigen (HLA)-matched donors. However, single-unit CB-HCT is limited by the insufficient cell dose and slow engraftment. To overcome this limitation, we combined a single-unit CB with third-party healthy donors’ bone marrow (BM) derived mesenchymal stromal cells (MSCs) to improve engraftment and injected intra-osseously (IO) to enhance homing. In this phase I clinical trial, six patients with high-risk hematologic malignancies were enrolled and received allogeneic HCT using reduced intensity conditioning regimens. The primary objective was to determine the engraftment rate at day 42. The median age of enrolled patients was 68 years, and only one patient was in complete remission at the time of HCT. The median CB total nucleated cell dose was 3.2x107 /kg. No serious adverse events were reported. Two patients had early death due to persistent disease and multi-drug resistant bacterial infection, respectively. Of the remaining four evaluable patients, all had successful neutrophil engraftment in a median of 17.5 days. No grade 3 or higher acute graft-versus-host disease (GvHD) was observed, and only one patient developed moderate-extensive chronic GvHD. In conclusion, IO co-transplantation of a single-unit CB and MSCs was feasible and resulted in a reasonable engraftment rate in these very high-risk patients.